Visual Detection of West Nile Virus Using Reverse Transcription Loop-Mediated Isothermal Amplification Combined with a Vertical Flow Visualization Strip - Cao, Zengguo; Wang, Hualei; Wang, Lina; Li, Ling; Jin, Hongli; Xu, Changping; Feng, Na; Wang, Jianzhong; Li, Qian; Zhao, Yongkun; Wang, Tiecheng; Gao, Yuwei; et al. (Frontiers in Microbiology, 2016)
West Nile virus (WNV) causes a severe zoonosis, which can lead to a large number of casualties and considerable economic losses. A rapid and accurate identification methodfor WNV for use in field laboratories is urgently needed. Here, a method utilizing reverse transcription loop-mediated isothermal amplification combined with a vertical flow visualization strip (RT-LAMP-VF) was developed to detect the envelope (E) gene of WNV. The RT-LAMP-VF assay could detect 102 copies/μl ofan WNV RNA standard using a 40 min amplification reaction followed by a 2 min incubationof the amplification product on the visualization strip, and no cross-reaction with other closely related members of theFlavivirus genus was observed. The assay was further evaluated using cells and mouse brain tissues infected with a recombinant rabies virus expressing the E protein of WNV.The assay produced sensitivities of 101.5TCID50/ml and 101.33 TCID50/ml for detection of the recombinant virus in the cells and brain tissues, respectively. Overall, the RT-LAMP-VF assay developed in this study is rapid, simple and effective, and it is therefore suitable for clinical application in the field.